The Acting Person on the U.S.-Mexico Border : Revisiting Karol Wojtyla’s Idea of Being a Neighbor - Irene Ludji (Indonesian Journal of Theology, 2020)
This article discusses the importance of being a neighbor, as understood through Karol Wojtyla’s idea of “the acting person,” in the context and experience of the migrants and humanitarian volunteers on the U.S.-Mexico border. There are three parts to this article. In the first part, I discuss the reality that migrants and humanitarian volunteers face at the U.S.-Mexico border. Migrants live in a liminal and violent space at the border, and the volunteers choose to enter this space to meet the vulnerable others. In the second part, I examine an idea presented by then-Cardinal Karol Wojtyla in his book The Acting Person. In the book─published in 1969 before he became Pope John Paul II in 1978─Wojtyla addresses the importance of being a neighbor through conscious participation in actions “together with others” for the achievement of the common good. In the third part, I present a critical reflection on the connection between migrants’ context and humanitarian work experience at the U.S.-Mexico border and Wojtyla’s idea of the acting person as a neighbor. By putting the idea of a neighbor in dialogue with the context of the U.S.-Mexico border, I intend to broaden Wojtyla’s thought to address the contemporary circumstances at the border.